1995
DOI: 10.3386/w5398
|View full text |Cite
|
Sign up to set email alerts
|

Natural Resource Abundance and Economic Growth

Abstract: pGIb!Ud M!P pe qss q99 M!J fl2 11.0W UJG!L bLeAlone MOL)C MG MOfl 9120 I!IG jO W9LJ1 IGII KGLU6L suq IGUU!IGL H9LU.2 IOL DGr0u 9MLGUC6 2flWWGL2 }OpGL K!Uä suq K022 reA!ue OL quqA 2psL!uä 9U GX9u2!AG swonu o suq bsLr!c!b9ue !U W HIID LG2G9LCJ LGLG9 IOL pe,btni C0WW6U2 KOpGI4 99LL0 'ioUä-%JJ9 16Gb BLS 0L0MP'. S1A9L lU2flG 101 IUGW9i0U9I DGAGI0bW9U 1SUfl9LA 4882 MG M12p O J9UJ(9SU .LSAIOL 1JjJ!2 IC 9 2flpC9uP9Il1 LGACGq AGI2IOU 0 OfiL GSLflGL bsbeL' KG2OflLCG2 suq E0U0W!C bnse VUSL Sfl U9flL9I LG2OflLCG2 19129 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

69
2,129
16
134

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,745 publications
(2,451 citation statements)
references
References 0 publications
69
2,129
16
134
Order By: Relevance
“…The negative relation between the natural resource abundance and economic growth is well documented in the literature (Sachs and Warner, 1995, 1997, 1999a,b, Sala-i-Martin, 1997, Doppelhofer et al, 2000. A number of theories were proposed to explain this negative link.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The negative relation between the natural resource abundance and economic growth is well documented in the literature (Sachs and Warner, 1995, 1997, 1999a,b, Sala-i-Martin, 1997, Doppelhofer et al, 2000. A number of theories were proposed to explain this negative link.…”
Section: Introductionmentioning
confidence: 91%
“…The spectrum of issues raised in the literature ranges from the issues of currency appreciation in the era of high resource prices and the subsequent "Dutch disease" effects that deteriorate the development of industrial sector of the economy (Corden and Neary, 1984;Sachs and Warner, 1995) to the political economy problems associated with the numerous nonproductive activities of economic agents provoked by the huge natural resource rents that undermine the institutional development of the economy and slow down economic development (Lane and Tornell, 1999;Auty, 2001) One of the channels that the literature addresses deals with the link between human capital development and natural resource abundance (Leamer et al, 1999;Gylfason 2001). The argument is based on the idea that resource intensive sectors absorb national savings while creating only a few eminently qualified jobs which leads to lower incentive of the society to educate their citizens compare to the societies with lower abundance in natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it may dampen long-term economic growth by damaging the balance of growth across different sectors of the economy. While pioneering empirical cross-country studies have established that natural resource abundance can have a negative impact on economic growth, which is known as a resource curse (Arezki and van der Ploeg, 2007;Brückner, 2010;Bulte, Damania & Deacon, 2005;Kronenberg, 2004;Rodriguez and Sachs, 1999;Sachs and Warner, 1995, 1997, 2001, the potential link between natural resource volatility and the volatility of growth has not been studied systematically yet.…”
Section: Introductionmentioning
confidence: 99%
“…After Habakkuk (1962) and Murphy et al (1989) claimed that growth depends on resource abundance, Sachs and Warner (1995) showed that resource abundance can also lead to poor economic performance: the 'curse of resources' hypothesis. The curse can be due to the fact that non-resource sectors are crowded out by overdevelopment of resource sectors ('Dutch disease', see Sachs and Warner, 1999), or can be explained by a rent-seeking argument (Tornell and Lane, 1999;Baland and Francois, 2000).…”
Section: Introductionmentioning
confidence: 99%